Evaluation of the Protoscolicidal Effectiveness of Hypertonic Saline, Silver Nitrate, Ethanol, Using Sponge Pad Method and Injecting into Fertile Hydatid Cysts - Kereshmeh Fakharzadeh Jahromi; Abdollah Rafiei; Mahmoud Rahdar; Amin Bahreini (Iranian Journal of Parasitology, 2022)
Background: We aimed to evaluate currently protoscolices agents by using two methods including injection and impregnated sponges with protoscolices agents.